PENERAPAN TEORI VAN HIELE SEBAGAI DASAR PENGENALAN GEOMETRI PADA SISWA DI SDN 045 TARAKAN - Dedi Kusnadi; AWilda Indra Nanna (Universitas Asahan, 2020)
The aim of this study was to examine of the application of Van Hiele as a basis for introducing geometry during teaching and learning at SDN 045 Tarakan. These learning process had been conducted by following the procedure of teaching geometry according to Van Hiele theory. The type of research used classroom action research with 27 students as research subjects. Data collected using teacher and student activity observation sheets. The result of the study learning of implementation had conducted in accordance with planes. In can be seen in the teacher’s activity had conducted aspect learning geometry effectively. The teacher able to utilize the learning media. For student activity, the students could response the teacher’s questions. Able to identify the learning of material effectively. The student able to identify the plane by using the learning media. So that application of Van Hiele theory had provided initial experience in understanding theory. Keyword: Geometry, Van Hiele, Theory Tujuan penelitian ini menelaah penerapan teori Van Hiele sebagai dasar pengenalan geometri selama kegiatan pembelajaran di SDN 045 Tarakan. Proses pembelajaran dilakukan dengan mengikuti fase-fase pembelajaran geometri menurut teori Van Hiele. Jenis penelitian ini menggunakan penelitian tindakan kelas dengan subjek penelitian 27 siswa. Data dikumpulkan menggunakan lembar observasi aktivitas guru dan siswa. Hasil penelitian menunjukkan pelaksanaan pembelajaran sesuai rencana, terlihat pada aktivitas guru yang melaksanakan fase pembelajaran geometri dengan baik, mampu mengelola kelas, dan memanfaatkan media pembelajaran. Untuk aktivitas siswa, siswa berani bertanya dan menjawab pertanyaan guru, siswa mampu menggali materi sifat bangun datar dengan baik, siswa mahir mengidentifikasi bangun datar dengan menggunakan alat peraga. Dengan demikian penerapan teori Van Hiele dapat memberikan pengalaman awal bagi siswa dalam memahami geometri.Kata kunci: Geometri, Teori, Van Hiele